1998
DOI: 10.3109/10826089809059341
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Substance Use among Adolescents: A Matrix of Prospective Predictors

Abstract: This paper reviews findings from 58 prospective studies of illicit substance use (ISU) among adolescents. It arranges 384 findings according to three types of influence (viz., social, attitudinal, and intrapersonal) and four levels of influence (viz., ultimate, distal, proximal, and immediate). The bulk of evidence reconfirms the importance of several predictors of ISU (e.g., intentions and prior substance-related behavior, friendship patterns and peer behaviors, absence of supportive parents, psychological te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
77
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(91 citation statements)
references
References 56 publications
9
77
0
5
Order By: Relevance
“…Overall, the findings of this study confirm the results of previous studies on ethnicity, ethnic identity, and drug use (Gilvarry, 2000;Waller, 2002, Marsiglia et al, 2001;Petraitis et al, 1998;Spooner, 1999). The findings advance our understanding of withingroup differences, specifically in reference to Mexican/Mexican American adolescents in the Southwest region.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, the findings of this study confirm the results of previous studies on ethnicity, ethnic identity, and drug use (Gilvarry, 2000;Waller, 2002, Marsiglia et al, 2001;Petraitis et al, 1998;Spooner, 1999). The findings advance our understanding of withingroup differences, specifically in reference to Mexican/Mexican American adolescents in the Southwest region.…”
Section: Resultssupporting
confidence: 88%
“…The link between substance use and academic achievement has been well reviewed and documented (Beman, 1995;Gilvarry, 2000;Hawkins et al, 1992;Petraitis et al, 1998;Spooner, 1999). Academic performance has been strongly associated with tobacco, alcohol, and drug use in preadolescents and adolescents (Abdelrahman et al, 1998;Dishion et al, 1999;Neumark-Sztainer et al, 1997;Stevens et al, 1996;Yarnold and Patterson, 1995).…”
Section: Academic Achievementmentioning
confidence: 99%
“…Initiating use at a younger age was significantly associated with more Dating back to 1978, Kandel found that associating with drug-using peers was a significant risk factor for initiating illicit drug use. Consistent with this prior research, according to Hussong (2002) and supported by numerous studies (e.g., Hawkins, Catalano, and Miller, 1992;Oetting and Beauvais, 1986;Petraitis et al, 1998;Copeland and Martin, 2004), the peer context is possibly the most salient, robust predictor of an adolescent's substance use. Involvement in a substance-using group tends to be associated with various forms of licit and illicit substance use (Chassin et al, 1986;Hawkins, Catalano, and Miller, 1992).…”
Section: Correlates Of Ecstasy Use Among Youth and Young Adultssupporting
confidence: 70%
“…The present study demonstrates the potential value of genetically informative strategies to clarify important developmental processes. The next challenge will be to expand these analyses to include the key externalizing outcomes in young adulthood, including antisocial behaviors and drug abuse, that we know from this (Jacobson et al 2002;Kendler et al 2007) and other samples (Hawkins et al 1998;Petraitis et al 1998) are predicted by levels of CD and PD in childhood and adolescence. Three plausible models for the role of additive genetic risk factors (A) on levels of symptoms of conduct disorder (CD) and peer deviance (PD) for the ages of 8-11, 12-14 and 15-17.…”
Section: Discussionmentioning
confidence: 99%